"THE EFFECTIVENESS OF USING MOTION AUDIOVISUAL MEDIA ON STUDENTS' ABILITY TO WRITE EXPLANATORY TEXTS FOR NURSING STUDENTS AT THE DELI HUSADA DELI TUA HEALTH INSTITUTE - Mona Fitri; Afrilius Simanjuntak (Jurnal Penelitian Keperawatan Medik, 2021)
Theoretical framework is a concept to see and explain phenomena that have become variables in research, which will used to analyze the data. Then the theoretical framework in This research will explain the independent variable and the dependent variable. The two variables sequentially are effectiveness use of motion audiovisual media and the ability to write text explanation. Effectivenessis the success of a business or action taken on something, which is success it is something that is expected by business actors or actors the action itself. So in this study, the effort or action in the form of the use of learning media, namely motion audiovisual media. This research was conducted at the Deli Husada Deli Tua Health Institute. This research using the experimental method with using two classes, namely the experimental class and the control class. Results or data that obtained in this study is effectiveness of use motion audiovisual media used researchers in learning writing explanatory text in class VIII 7th Medan Junior High School year lesson 2019/ 2020. Ability score student write explanatory text in experimental class average 75.97 with good category, and in class control average 65.8 of course with sufficient category. Value earned with using motion audiovisual media in the experimental class with enough category 1 student (3.33%), good category 11 students (36.67%), very good category 18 students (60%). Based on these data, it can be oncluded that students are very good at choosing a writing theme and developing writing according to the specified theme or topic. This ability is of course on the effectiveness of using motion audiovisual media.